การผลิตโฟมวัสดุผสมอะลูมิเนียม-ซิลิคอนคาร์ไบด์ที่มีโพรงอากาศแบบเปิดโดยการแทรกซึมด้วยความดัน - เอกภักดิ์ วิเชียรรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The objective of this research is to study the production of silicon carbide (SiC) particulated aluminium matrix composite foams by investment casting technique and to investigate the effects of SiC particle content and pore sizes on macrostructure, microstructure and mechanical properties of the foams. Pure Al and AC3A Al alloy, mixed with SiC particles, have been used to produce open-cell composite foams with of 8, 12 and 20 ppi polyurethane foam preforms at 1200°C, assisted with 1.2 bar infiltration pressure. The 20 x 20 x 20 mm of sectioned foams were compressed at the cross-head speed of 1 mm/min. It is found that this process can produce AC3A composite foams for all pore sizes, but for pure Al, 12 and 20 ppi foams cannot be produced. Both types of foams are well replicated. SiC particles are well dispersed in strut and plateau border of all foams. Clusters of SiC particles in matrix and strut surface are found in 4 and 5 wt.%SiC additions. Increasing SiC addition results in increasing relative density and mechanical properties, such as yield strength, plateau stress, energy absorption and hardness. Mechanical properties of AC3A composite foams are much higher than pure Al composite foams. AC3A composite foams with 12 ppi pores have the best mechanical properties, followed by 20 and 8 ppi pores respectively.